Race and babassu coconut breakers in Maranhão: Race, economic development projects and babassu coconut breakers in 20th century Maranhão (Simbiótica. Revista Eletrônica, 2023)
This article aims to situate the efforts of black babassu coconut breakers around making their blackness positive. To do so, it will demonstrate how the racialization of blackened bodies is part of the knowledge production about the potentialities of the babassu economy in Maranhão. In turn, in contrast to these analyses, these black coconut breakers women have been activating memories, producing life and making incessant efforts in the midst of a declared race war. Keywords: babassu coconut breakers; racial belonging; babassu economy; Maranhão